Reduction of leaky wave coupling in a superstrate loaded antenna using metamaterial. Issue 17 (22nd November 2018) - Ghosh, Jeet; Mitra, Debasis; Bhadra Chaudhuri, Sekhar Ranjan
ABSTRACT: In this paper, an approach is presented for reducing leaky wave coupling of superstrate loaded slot array using zero index metamaterial structure. The dielectric superstrate generally aims at increasing the directivity of the antenna by the generation of leaky wave. In another aspect, the leaky wave reduces the isolation between radiating elements in multiple antenna system. Here, the metamaterial has been used to mitigate the mutual coupling by reducing the generation of the leaky wave. By the help of this approach, the isolation is improved throughout the operational bandwidth and maximum 15 dB isolation improvement is achieved with an edge to edge distance of 4 mm between radiating elements.